A Narrative Inquiry of Three Chinese International Students’ Academic Adjustment Experiences at Canadian Universities - Huang, Ju; Guo, Haojun; Zhou, Qiutong (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
There is an increasing number of Chinese graduate students who study in Canada and have quite different educational backgrounds. Despite a large number of studies attending to the challenges and difficulties they encountered in life and study, not much research narratively explores Chinese international students’ academic adjustment experiences in graduate programs in Canada. To fill the gap, this research makes a narrative inquiry into three Chinese international students’ academic adjustment in the graduate and doctoral programs of two universities in Ontario, Canada. The three-dimensional framework (Clandinin, 2006) is employed to tell and retell their stories. Their narratives have revealed the importance of their native languages and how their past experiences before they came to Canada influenced their academic adjustment. The Eastern and Western cultures have had a lasting effect on their personal and professional development. In addition, they have played multiple roles as Chinese international students, novice researchers, and future educational practitioners.